Pengaruh Jiwa Kewirausahaan Dan Lokasi Terhadap Keberhasilan Usaha Kelapa Parut Ibu Maritha Di Tenggarong Seberang - Syahruddin S (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2017)
Abstract:The purpose of this study is to determine the extent to which the influence of Entrepreneurship and Location Spirit Affects the Success of the Business of Grated Coconut Mrs. Mahrita In Tenggarong Seberang and to Know Which Variables Has Dominant Influence To The Success Of The Scarring Business Of Ibu Mahrita In Tenggarong Seberang. One of the Small and Medium Industries in Tenggarong City, especially in Tenggarong Seberang is the business of Mrs. Mahrita Head of Scars which is located at Kusuma Rt. 02. No 26 Teluk Dalam Village Tenggarong Seberang Subdistrict. This business has enormous potential where it takes more than 1000 heads every month to serve consumers. Data analysis model, in accordance with the object of research is on the Business of Coconut Grated Mrs. Mahrita In Tenggarong Seberang where the independent variables used two variables, the analysis used to prove the hypothesis in this study is a quantitative analysis with multiple regression model with a population of 294 consumers and samples As many as 70 consumers. The results showed that the entrepreneurship spirit variable (X1) and location (X2) simultaneously (simultaneously) were able to show its influence on business success. Then the first hypothesis states that "the entrepreneurial and location soul variables have a significant effect on the success of the Kelan Kelut Usaha Ibu Mahrita Di Tenggarong Seberang" is accepted and proven to be true. From both test results partial correlation above visible value of entrepreneurial soul variable the greatest influence compared to location variable, so that entrepreneurship soul variable is the most dominant variable affecting the success of the business. From the description, it can be concluded that the second hypothesis in this study "That Location Variables Influential Dominant to the success of the Business of Coconut Grated Mrs. Mahrita In Tenggarong Seberang" in rejected and not proven truth.Keywords: Soul Entrepreneurship, location, Success